Post-competition blood lactate in disabled swimmers - Roi, G. S.; Cerizza, C. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
The time taken to cover 50 m in freestyle swimming and the postcompetition blood lactate levels were measured in healthy and disabled swimmers. The results of this study show that disabled swimmers take more time and accumulate a lower lactate per unity of time than healthy subjects. These differences can be due to the lower muscular mass utilized by disabled swimmers and to the particular technique they employ according to their handicap. Furthermore the high values of lactate found at the end of the race indicate that the contribution of the anaerobic energetic sources is important in disabled athletes too.